P466Coronary vascular smooth muscle cell proteins in the hypercholesterolemic swine: plaque-related markers of accelerated atherogenesis. (15th July 2014) - Rocchiccioli, S; Cecchettini, A; Ucciferri, N; Viglione, F; Citti, L; Parodi, O; Trivella, MG; Pelosi, G
Abstract: Purpose: A major drawback in atherogenesis research is the difficulty of investigating early phase of disease in the clinical context. A high-cholesterol diet animal model of coronary artery disease was exploited in order to characterized by histomorphometry early stages of disease and to identify plaque-related markers of accelerated atherogenesis. The comparison of the secretomes from atherosclerotic and healthy coronaries led to the identification of differentially released proteins. Histology and immunohistology validated the proteomics results, allowing the tissue localization of interesting factors and correlating the released proteins with the lesion stage. Methods: Histological characterization of segmented main coronary arteries was performed in high cholesterol (HCD) and standard diet treated (SD) farm pigs and histomorphometry indexes (intimal thickness and lesion area wall percent) of all lesions were estimated. Right coronary artery (RCA) segments from HCD and SD animals were incubated for 24 hrs in serum-free medium. Released proteins were digested with trypsin and analysed by HPLC coupled with mass spectrometry. Immunohistology was performed for the most relevant differentially expressed proteins. Results: Atherosclerotic lesions (from fatty streaks to fibrofatty atheromas) of all 3 main coronary arteries have been observed in HCD group, with intimal thickening of 0, 52±0, 38 mm and lesion area of 40 ± 26%. Proteomics analysis of secreted factors identified 200 actively secreted proteins, of which, 10 were up-released as compared to SD and 6 were significantly related to morphometric indexes of ATS severity and burden. Among these, Chitinase-3-like protein 1 was validated by immunostaining. This last co-localizes with alpha-SM actin showing a distinctive tissue distribution that resulted significantly correlated to secretome expression both in early (fatty streaks) and atheromatous lesions. Conclusions: In the accelerated coronary atherogenesis swine model, tissue factors related to ATS stages and overall burden have been identified. These factors are strictly linked to VSMC phenotype changes and cell activation, thus they may be regarded as specific lesion-related molecules and are exploitable as potential biomarkers of atherosclerosis progression.